Notes on the genus Astinus Stål (Heteroptera: Reduviidae: Harpactorinae) from Vietnam, with the description of the female of Astinus intermedius Miller - Truong, Xuan L.; Zhao, Ping; Cai, Wanzhi Z. (Zootaxa, 2006)
Two species of Astinus Stål of the reduviid subfamily Harpactorinae (A. siamensis and A. intermedius) from Vietnam are recognized and keyed. Astinus intermedius Miller, 1954 is reported for the first time from Vietnam. The female of A. intermedius is described. The dorsal habitus, head and pronotum, genital structures, and other diagnostic morphological features of the two species are illustrated.